Episteme do Inefável: razões da irracionalidade na univocidade mística - Altran, José (2014)
The dissertation suggests that an epistemology that listen to irrationality is relevant to face perennial obstacles in the philosophy of science, against which many objects collide. This seems to be an especially useful alternative in the sciences of religion, where we see ourselves immobilized by rationality when engaging researches that are related to their typically unspeakable phenomena. The mystical experience, often taken as the basis of religion, is a scenario that often brings amid its ineffability a sense of univocity - which is, precisely, the horizon of academic making. Would this ineffable hold an episteme? Following the publications of Marcelo Dascal, Henri Bergson and others, it is argued that, overcoming asymmetric impositions of epistemic legitimacy that inhibit controversies, we could find in bergsonian intuitionism a way toward these subjects as elusive as dangerous, since they put the rationality as a functional pillar for science and irrationality as a metaphysical pillar to reality itself. The transformations that the mystics brought to the world throughout history could be taken as signs that not only the irrationality was their compass, but also that it can bring extremely desirable outcomes for humanity, althought impelled by unspeakable epiphanies. Our aim is to gradually create lucid foundations for the study of alleged mystical univocities that invariably would become relative under the eyes of reason